A Liberal Maritime Power as Any Other? The Soviet Union during the Negotiations of the Law of the Sea Convention. (26th May 2021) - Thévenin, Pierre
Abstract: This article examines the role played by the Soviet Union during the negotiations of the United Nations Convention on the Law of the Sea. The author argues that since its transformation into a maritime power in the 1960s, the USSR defended a liberal conception of the law of the sea, similar to that promoted by the West with which it cooperated in order to resist attempts by developing states to increase coastal state sovereignty on the high seas and centralize exploitation of the deep seabed's resources. To demonstrate its thesis and reassess the findings of the existing literature, this article draws upon the travaux préparatoires of the Law of the Sea Convention, as well as newly available fonds from the French Diplomatic archives.